Griscelli syndrome Type 2: A report of rare case - Chandramohan Kudligi; Pradeep Vittal Bhagwat; Mary Zothanpuii Chhangte; Vidya Kuntoji; Sujata Giriyan; Veena Andanappanavar (Clinical Dermatology Review, 2017)
Griscelli syndrome (GS) is a rare autosomal recessive disorder characterized by pigmentary dilution of the hair and skin. Three different types (1–3) caused by mutation in three different genes have been described. GS2 is characterized by partial albinism, immunodeficiency, organomegaly, and hemophagocytic lymphohistiocytosis (HLH). Long-term prognosis of GS2 is poor, and in most cases, it leads to death within the first decade of life. GS2 is most common among three types with 11 cases reported from the Indian literature. We report a case of GS2 which was diagnosed well before the development of life-threatening HLH.